Children Rights in France - Mehmet Rıfat Tınç (İstanbul Hukuk Mecmuası)
Since the second half of the 19th century, French law has recognized the child as a legal person who has rapidly attained autonomy due to social changes. Due to child’s limited legal capacity, the French legal order, as in many other legal systems, treats him or her as an object of law needing protection, rather than as a complete legal subject. Recent changes in the family concept, such as the advancement of fundamental rights; the legal status of extramarital partnerships; the possibility of same-sex marriages; and the expansion of children’s rights in international agreements, have influenced the development of French juvenile law; the evolution of the child as a legal person; and his progression from a legal object to a legal subject in contemporary law. Even if childhood remains a legal concept that needs to be protected, children’s ability to operate their own rights increases and they become nearly a legal subject. In some cases, they can even acquire a full legal personality just like an adult. However, despite all the progress made so far, the child’s legal status has not been fully realized, nor have the existing children’s rights been fully implemented.